2006
DOI: 10.1159/000090526
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Plasma Levels Are Significantly Elevated in Patients with Cerebral Arteriovenous Malformations

Abstract: Background: Since growth and de novo generation of cerebrovascular malformations were demonstrated, a strictly congenital model cannot be further supported as unique factor in the pathogenesis of cerebral arteriovenous malformations (AVMs). Vascular endothelial growth factor (VEGF) has previously been demonstrated to be highly expressed in AVMs by immunohistochemical methods. However, systemic VEGF levels have not been analysed previously. This study aimed to investigate VEGF plasma concentrations as a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 49 publications
0
21
0
2
Order By: Relevance
“…One study demonstrated significantly higher levels of VEGF in patients with AVMs compared with a control group. 13 Patients with hereditary hemorrhagic telangiectasia (HHT) have an increased prevalence of AVMs and also have elevated levels of VEGF. 14,15 Hypoxia is known to stimulate expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated significantly higher levels of VEGF in patients with AVMs compared with a control group. 13 Patients with hereditary hemorrhagic telangiectasia (HHT) have an increased prevalence of AVMs and also have elevated levels of VEGF. 14,15 Hypoxia is known to stimulate expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study reported a significant increase in circulating VEGF levels in AVM patients compared to healthy controls. 40 Increased expression of circulating VEGF has also been associated with other cerebrovascular disorders including intracranial aneurysms, 41 dural arteriovenous fistulas, 21 and vasospasm after subarachnoid hemorrhage. 5 VEGF expression is regulated by numerous factors, most significantly hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,20,22 More recently, one study reported significantly elevated circulating VEGF levels in AVM patients compared to healthy controls. 40 VEGF is a dimeric heparin-binding glycoprotein and mediates angiogenesis under both physiological and pathological conditions. 31 It is a highly specific and potent mitogen of vascular endothelial cells, promotes endothelial cell survival and migration, and increases microvascular permeability.…”
mentioning
confidence: 99%
“…Importantly, these AVMs only occurred after stimulation with vascular endothelial growth factor (VEGF) [28]. Indeed, VEGF promotes vascular proliferation and is markedly increased in patients with cerebral AVM [29]. However, VEGF stimulation alone has never been shown to induce de novo AVM formation in animal models.…”
Section: The Casementioning
confidence: 99%